The Correlation between The Vocabulary Mastery and Writing Skills of the Ninth Graders of SMP Negeri 1 Bandongan - Annisrina Fajri Nugraheni; Gilang Fadhilia Arvianti; Taufik Arochman (Seltics Journal: Scope of English Language Teaching Literature and Linguistics, 2024)
Four language skills are needed to master a language: listening, reading, speaking, and writing. Two aspects are needed to communicate in written form: vocabulary mastery and writing skills. Someone needs writing skills and extensive vocabulary knowledge to create good writing. Even so, it was found that there were still students who had difficulties in translating words from Indonesian to English and vice versa, challenges in using the right words, and problems in constructing sentences in English. In addition, some students still have limited knowledge of vocabulary. This study focused on finding the students’ vocabulary mastery level, writing skills level, and the correlation between vocabulary mastery and writing skills. A person will master four language skills, including writing, easier if they have a broad vocabulary. The more comprehensive the vocabulary knowledge, the more vocabulary will be used in writing; hence, the vocabulary used in the writing will be more varied. Correlation research was used in this study. The study population was 9th graders of SMP Negeri 1 Bandongan, and the sample was 29 students from class 9B at SMP Negeri 1 Bandongan. The study instruments were a vocabulary test and a writing test. The instruments were derived from previous research. The data taken was analyzed using a correlation test with SPSS. The results of this study show no significant correlation between vocabulary mastery and writing skills with the Sig value. (2-tailed) 0.145 > 0.05. Furthermore, the correlation coefficient is 0.278. Hence, the correlation between vocabulary mastery and writing skills was low. This study suggests that teachers and students focus on learning and mastering vocabulary and other aspects that influence writing ability and the writing itself.